2014
DOI: 10.1590/s0100-7203201400040003
|View full text |Cite
|
Sign up to set email alerts
|

Gordura corporal total e do tronco e o desempenho da marcha em mulheres na menopausa

Abstract: Postmenopausal women with a greater amount of trunk fat tended to have impaired gait performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…Porém, quando estas realizam exercícios físicos, os resultados relacionados à autopercepção de saúde mostram-se positivos. Essa influência pode ocorrer devido à prática regular de exercícios físicos, diminuindo os efeitos dos distúrbios causados pelo período da menopausa, em que as mulheres sofrem diminuição de massa magra e aumento da gordura corporal, fatores que acentuam o risco para doenças crônicas e declínio funcional (SIMS et al, 2013;FORTALEZA et al, 2014).…”
Section: I S C U S S ã Ounclassified
“…Porém, quando estas realizam exercícios físicos, os resultados relacionados à autopercepção de saúde mostram-se positivos. Essa influência pode ocorrer devido à prática regular de exercícios físicos, diminuindo os efeitos dos distúrbios causados pelo período da menopausa, em que as mulheres sofrem diminuição de massa magra e aumento da gordura corporal, fatores que acentuam o risco para doenças crônicas e declínio funcional (SIMS et al, 2013;FORTALEZA et al, 2014).…”
Section: I S C U S S ã Ounclassified
“…16 In addition, Fortaleza et al showed that only abdominal fat, but not total body fat or percentage of body fat, is associated with impairment of physical capacity in elderly women. 24 During aging there are changes in body composition, such as increased body fat and decreased muscle mass and strength. 23 The association between low muscle mass and strength and excess fat is termed sarcopenic obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Due to metabolic changes, postmenopausal women experience an accumulation of total, hip, and trunk fat, which affects posture, 28 leading to an increase in the risk of falls and fractures, 3 and this condition may be associated with frailty. 29 The CT is an efficient training strategy for changing body composition, increasing lean mass, and reducing fat, especially in the trunk.…”
Section: Palavras-chavementioning
confidence: 99%